1995
DOI: 10.1111/j.1432-1033.1995.tb20802.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the Metal‐Bridging Proton‐Donor His63 Residue in Human Cu, Zn Superoxide Dismutase

Abstract: The bridging His63 residue in human Cu, Zn superoxide dismutase, which binds both metals, has been replaced by a Cys residue. The mutant protein has been purified from Escherichia coti and appears to be a normal dimer. Spectroscopic techniques (electronic spectroscopies, EPR, nuclear magnetic relaxation dispersion) show that Cys63 binds the zinc ion, but not the copper ion, and that the latter is probably five co-ordinated with three histidine ligands and two water molecules. The reduction potential of the cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…406 Banci et al reported substitution of the bridging His63 in CuZnSOD with Cys, showing that Cys63 preferably binds to Zn(II) over Cu(II), leaving a five coordinate copper center where copper is coordinated to three His and two water molecules. 409 These studies indicate that the simple incorporation of a Cys ligand at the copper center in CuZnSOD is not sufficient to construct a T1Cu site. When designing metal-binding sites, one needs to consider additional factors, including geometric constraints and secondary coordination sphere interactions.…”
Section: Protein Redesignmentioning
confidence: 99%
See 1 more Smart Citation
“…406 Banci et al reported substitution of the bridging His63 in CuZnSOD with Cys, showing that Cys63 preferably binds to Zn(II) over Cu(II), leaving a five coordinate copper center where copper is coordinated to three His and two water molecules. 409 These studies indicate that the simple incorporation of a Cys ligand at the copper center in CuZnSOD is not sufficient to construct a T1Cu site. When designing metal-binding sites, one needs to consider additional factors, including geometric constraints and secondary coordination sphere interactions.…”
Section: Protein Redesignmentioning
confidence: 99%
“…404 Although there is no sequence or active site homology between the two systems, researchers intended to introduce a T1Cu site in CuZnSOD by mutating an active site His residue into a Cys. 405409 On the basis of the crystal structure of the active site in CuZnSOD, there are three types of His residues coordinating to the metal ions: His residues that are only coordinated to copper, that is, copper-His (His46, 48, and 120); His that are only coordinated to Zn(II) (zinc-His, His71, and His80); and a bridging His residue that binds to both copper and zinc ions (His63). Besides these three His residue types, an additional water molecule is coordinated to copper and an Asp residue to zinc.…”
Section: Protein Redesignmentioning
confidence: 99%
“…The reducing potential of APP142-166 for Cu(II) was identified by the decreased signal of Cu(II) in EPR analysis with a 30-fold molar excess of peptide to CuCl 2 (Figure 2A). A peptide, that carried amino acid substitutions at cysteines and the Cu-coordinating histidines, showed an EPR spectrum of a regular type II copper site (29), with an axial g ⊥ ()2.06) feature and with a hyperfine coupling A | of 142 × 10 -4 cm -1 and a g | ) 2.28 (data not shown). These results are consistent with EPR-nondetectable Cu(I) as an EPR-silent complex and corroborate our previous findings of Cu(I) formation by APP using bathocuproine disulfonate as an indicator molecule for Cu(I) (15).…”
Section: T H Imentioning
confidence: 99%
“…138 The bridging histidine in CuZnSOD was also replaced with a cysteine by Banci et al, but the resulting protein did not display any S-to-Cu(II) charge transfer absorption, indicating the lack of a Cu-cysteine bond. 140 These studies demonstrated that both the cysteine ligand and the geometry define the structural and functional properties of type 1 blue copper proteins.…”
Section: From a Type 2 Copper Protein To A Type 1 Bluementioning
confidence: 98%